The Predation behaviour and biology of predator Sycanus aurantiacus (Hemiptera: Reduviidae) on the different larvae of Tenebrio molitor L. and Crocidolomia Pavonana FAB. - YULIADHI, KETUT AYU; SEDANA, AGUS PUTRA; SUDIARTA, I PUTU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
The Predation behaviour and biology of predator Sycanus aurantiacus (Hemiptera: Reduviidae) on the different larvae of Tenebrio molitor L. and Crocidolomia Pavonana FAB   Sycanus sp. belongs to the family Reduviidae which is a fairly large family and it’s known to be a predator of a killer or blood-sucking ladybug. The research to determine aspects of biology predators Sycanus sp. in the key pests of cabbage plants and larvae Tenebrio molitor , as well as know the rate of predation imago Sycanus sp. The research was conducted in Laboratory Integrated Pests and Disease Control  of Agroecotechnology Program Study Faculty of Agriculture Udayana University Bali. Predator Sycanus sp. obtained from the land planting cabbage at Pancasari Village, Buleleng. The prey species used are C. pavonana larvae and T. molitor . Larvae C. pavonana obtained from lands cabbage planting in vegetable center and larvae T. molitor obtained from local market around Tabanan regency. The results showed that the life cycle of Sycanus sp. in prey C. pavonana is longer that is 104 – 113 days compared with prey T. molitor is 88 – 99 days.    Longevity of imago female 70,4 ± 7,88 day and imago male 94,9 ± 5,04 day in prey C. pavonana , whereas longevity of imago female in prey T. molitor 83,1 ± 5,00 day and imago male 106,9 ± 10,46 day.